2013
DOI: 10.1111/jpy.12073
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of iodide in the marine haptophyte Isochrysis sp. (T.ISO) driven by iodide oxidation

Abstract: Uptake of iodide was studied in the marine microalga Isochrysis sp. (isol. Haines, T.ISO) during short-term incubations with radioactive iodide ((125) I(-) ). Typical inhibitors of the sodium/iodide symporter (NIS) did not inhibit iodide uptake, suggesting that iodide is not taken up through this transport protein, as is the case in most vertebrate animals. Oxidation of iodide was found to be an essential step for its uptake by T.ISO and it seemed likely that hypoiodous acid (HOI) was the form of iodine taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…However, the dependence of perox expression on environmental iodide (and not iodate), as revealed by threshold mRNA abundance and the response to H 2 O 2 , indicates that this gene could be a putative haloperoxidase. A previous study of our group indicated that iodide uptake in T. lutea could possibly be promoted by an enzymatic oxidation using H 2 O 2 (van Bergeijk et al, 2013). The similarity of perox with peroxidase-cyclooxygenases in metazoans and its origin by HGT, as previously discussed, makes this gene a good candidate to participate in iodide metabolism processes such as uptake and organification and it could thus also have an impact on the biosynthesis of TH-like-compounds.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, the dependence of perox expression on environmental iodide (and not iodate), as revealed by threshold mRNA abundance and the response to H 2 O 2 , indicates that this gene could be a putative haloperoxidase. A previous study of our group indicated that iodide uptake in T. lutea could possibly be promoted by an enzymatic oxidation using H 2 O 2 (van Bergeijk et al, 2013). The similarity of perox with peroxidase-cyclooxygenases in metazoans and its origin by HGT, as previously discussed, makes this gene a good candidate to participate in iodide metabolism processes such as uptake and organification and it could thus also have an impact on the biosynthesis of TH-like-compounds.…”
Section: Discussionmentioning
confidence: 66%
“…In addition to its nutritional value, T. lutea is a microalga that accumulates thyroid hormone (TH)-like compounds (Heyland and Moroz, 2005), indicating a particular iodide-related metabolism, what confers novel functional characteristics. Previous data of our group demonstrated this microalga is able to incorporate iodide from the environment after oxidation by enzymatic (haloperoxidase-mediated) or non-enzymatic ways (catalyzed by iron) (van Bergeijk et al, 2013(van Bergeijk et al, , 2016. Moreover, a fraction of intracellular iodine is organified as TH-like hormones (Heyland and Moroz, 2005).…”
Section: Introductionmentioning
confidence: 81%
“…Accumulation of iodine in other algal species and diatoms has also been demonstrated (Manley 2009, Osterc and Stibilj 2012, Shimura et al 2012, Thorenz et al 2014, van Bergeijk et al 2013). Regardless of the species, uptake appears to occur through the mechanism of a haloperoxidase, with or without hydrogen peroxide.…”
Section: A43 Iodine Bioaccumulationmentioning
confidence: 94%
“…There is currently hardly any knowledge if and how this process takes place in natural seawater. Estimates of the lifetime of iodide due to oxidation in natural seawater range between less than 6 months and 40 years (Campos et al, 1996;Edwards and Truesdale, 1997;Tsunogai, 1971). Reported abiotic rates are too slow to explain the shorter lifetimes, so biogenic iodide oxidation driven by phytoplankton (Bluhm et al, 2010) or bacteria (Amachi, 2008;Fuse et al, 2003;Zic et al, 2013) has been suggested, but there remains great uncertainty surrounding this process (Truesdale, 2007).…”
Section: Introductionmentioning
confidence: 99%